THE INFLUENCE OF THE WORK ENVIRONMENT ON EMPLOYEE MORALE AT THE SAMSAT OFFICE IN THE GOWA REGION - Nur Acikin; Muchriady Muchran; Syahidah Rahmah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study aims to analyze the influence of the work environment on employee morale at the Gowa Regional SAMSAT Office. Using a quantitative research design, the study involved a saturated sample of 43 employees, representing the entire population of staff working at the office. Data were collected through structured questionnaires and analyzed using simple linear regression with SPSS version 27. The results show that the work environment has a positive and significant effect on employee morale, indicated by a regression coefficient of 0.683 with a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.608 demonstrates that 60.8% of the variation in employee morale is explained by the work environment, while the remaining 39.2% is influenced by other factors not examined in this study. These findings highlight the importance of creating a conducive work environment—through improvements in workspace conditions, temperature control, and interpersonal relationships—to enhance employee morale and productivity.